Sedação em unidade de terapia intensiva: associação entre interrupção diária, eventos adversos e mortalidade - Barbosa, Taís Pagliuco (2017)
Sedation and analgesia in the intensive care unit collaborate in the treatment of patients in a serious condition, as it improves respiratory discomfort and adaptation to invasive mechanical ventilation, guaranteeing greater safety. However, excessive sedation is associated with prolonged mechanical ventilation, increased rates of delirium, and mortality. Objective: to associate the profile, sedation level, interruption criteria and mortality of patients on mechanical ventilation, daily discontinuation of sedation and associated with reports of adverse events. Method: the first step consisted of a prospective, longitudinal and quantitative study in two intensive care units, with 204 patients, using the Richmond Agitation-Sedation Scale and the Sepsis Related Organ Failure Assessment. Associated with daily withdrawal from sedation with adverse events. Tukey, Pearson and Chi-square tests were used. Results: The majority were male, surgical, with a mean stay of 10.7 days. The mean sedation was -2.45 (moderate) and the mortality was 15.8 (high risk). There was a statistical correlation between death in patients with deep sedation and sensitivity in relation to the discharge of those who suffered daily discontinuation of sedation. In deep sedation, approximately half, sedation was not disconnected daily, and with mild sedation, too. There were 28 adverse events in those with deep sedation, and 13 in mild, with pressure injury. Conclusion: The majority of the patients were male, 40 to 60 years old, surgical, in sedoanalgesia with fentanyl, midazolam and propofol, sedation time of one to five days, without daily interruption of drugs due to hemodynamic instability and order Not correlating statistically with the profile and level of sedation. The daily interruption of sedation guided by the Richmond Scale helps to control sedation, which favors the treatment and recovery of the patient, but it was not configured as an independent factor to predict mortality. Also, adverse events were not associated with daily discontinuation of sedation, but with work processes involving nursing care to the patient.